2008
DOI: 10.1007/s00125-008-1009-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of retinol-binding protein 4 in women with and without gestational diabetes

Abstract: Aims/hypothesis Pregnancy is characterised by temporarily increased insulin resistance. Gestational diabetes occurs when pancreatic beta cell function is unable to compensate for this insulin resistance. Retinol-binding protein 4 (RBP4) could be related to insulin resistance. We hypothesised that RBP4 is elevated in gestational diabetes. Methods Serum RBP4, transthyretin and retinol were crosssectionally measured in 42 women with gestational diabetes and 45 pregnant controls. Of these, 20 women with and 22 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 43 publications
4
73
3
2
Order By: Relevance
“…[38][39][40] Accordingly, women with gestational diabetes have also been suggested as a group in risk of presenting reduced VA levels. 4 In accordance with Basu et al, (1997) 38 among interfering factors in seric vitamin A concentration, the presence of DM does not seem to affect ingestion neither intestinal absorption. This way, the deficient state observed must be related to the vitamin's impaired transportation.…”
Section: Vitamin A: Metabolism and Functionssupporting
confidence: 77%
See 1 more Smart Citation
“…[38][39][40] Accordingly, women with gestational diabetes have also been suggested as a group in risk of presenting reduced VA levels. 4 In accordance with Basu et al, (1997) 38 among interfering factors in seric vitamin A concentration, the presence of DM does not seem to affect ingestion neither intestinal absorption. This way, the deficient state observed must be related to the vitamin's impaired transportation.…”
Section: Vitamin A: Metabolism and Functionssupporting
confidence: 77%
“…49 Considering that the presence of gestational diabetes aggravates the tendency to VAD development in these women, the provision of proper quantities of this vitamin for their infants will be damaged, making them vulnerable to presenting limited stock of vitamin A in the body. 4,6,34 This way, this nutritional disorder may cause an increase in mortality, morbidity and blindness in these children. It is known then that pre-school children with deficient vitamin A reserves in the body present a higher risk of death by diarrhea, respiratory infections, and chicken pox than children with adequate vitamin A state, since it has a protective role against these complications.…”
Section: Vitamin A: Deficiency and Diabetes Mellitusmentioning
confidence: 99%
“…These observations coupled with direct effects of RBP4 demonstrated in animal and cell culture models (5, 13) imply a strong role of RBP4 in obesitymediated insulin resistance. Recently, extensive trials in insulinresistant adults and children from multiple ethnic backgrounds revealed a strong association between plasma RBP4 concentrations with insulin resistance, obesity, and metabolic syndrome components (16)(17)(18)(19)(20). In addition, interventions that ameliorate insulin resistance in humans also reduced plasma RBP4 levels (11,14,(21)(22)(23).…”
Section: Plasma Rbp4 Ttr and Retinol Levels In Type 2 Diabetesmentioning
confidence: 99%
“…In appropriate nutrient conditions, 90% of circulating RBP4 is connected to retinol (RBP4 concentration in adults is 2-3μM) (Bellovino et al 2003 (Metzger et al 2007). Similar to Diabetes Mellitus type 2, GDM is associated with both insulin resistance and the decreased function of β-cells, which are unable to meet the increasing organic needs for insulin (Krzyzanowska et al 2008). It occurs in 1-14% of all pregnancies depending on the population studied, and it is associated with the increased perinatal morbidity and mortality (Sociedade Brasileira de Diabetes 2009).…”
Section: Introductionmentioning
confidence: 99%